The correlation between thyroid status parameters and prolactin levels in reproductive-age women with autoimmune thyroiditis and subclinical hypothyroidism - Yu.V. Buldygina; Yu.I. Beliakova; M.M. Vatsyk; H.M. Terekhova (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Patients with primary hypothyroidism often exhibit elevated thyrotropin-releasing hormone levels, potentially leading to hyperprolactinemia, which manifests as galactorrhea-amenorrhea. However, data on prolactin (PRL) content in subclinical hypothyroidism are inconsistent due to variations in study populations, sample sizes, and methodologies. In some studies, it has been found that hyperprolactinemia is a rare disorder in subclinical hypothyroidism, but there are reports of its fairly high prevalence in subclinical hypothyroidism — in 0–40 % of patients. This study purposed to assess PRL levels in reproductive-age women with autoimmune thyroiditis (AIT) and investigate correlations between PRL and thyroid hormone levels. Materials and methods. PRL level was analyzed in women with AIT in states of euthyroidism and subclinical hypothyroidism. Results. Findings revealed significantly elevated PRL in women with AIT compared to controls (18.24 ± 1.61 vs. 12.24 ± 1.64 ng/mL; p < 0.05). A Spearman regression analysis identified a significant negative correlation between PRL and free thyroxine (Spearman R = –0.27; p = 0.043), indicating a stronger association than between PRL and thyroid stimulating hormone (TSH). Analysis of PRL content depending on TSH levels showed that PRL significantly differed in patients with euthyroidism and subclinical hypothyroidism on the background of AIT (16.48 ± 1.46 vs. 25.45 ± 5.29 ng/ml; p < 0.05). No differences in PRL levels were observed among euthyroid patients with AIT based on TSH levels. Conclusions. PRL levels were significantly higher in women with AIT than in controls (18.24 ± 1.61 vs. 12.24 ± 1.64 ng/mL; p < 0.05). Women with subclinical hypothyroidism and AIT had significantly higher PRL levels than euthyroid women with AIT (25.45 ± 5.29 vs. 16.48 ± 1.46 ng/mL; p < 0.05). No statistically significant changes in prolactin levels were observed in patients with autoimmune thyroiditis and euthyroidism in TSH levels above 2.5 mIU/L compared to the control group (p > 0.05). A significant negative correlation between PRL and free T4 (Spearman R = –0.27; p = 0.043) indicates a more sensitive relationship compared to that between PRL and TSH.